Dynamic simulation of the energy consumption and carbon emissions for domestic hot water production in a touristic region. (25th June 2022) - Sousa, Vitor; Meireles, Inês
Abstract: At a buildings' level, domestic hot water consumption is amongst the most relevant examples of the water-energy nexus. As such, understanding its drivers and forecasting domestic hot water and associated energy consumption are of paramount importance for decision making from the individual household level to a national, or even international, sustainability policy level. However, detailed end-use measurements of either energy or water are seldom available and large scale (city, region or country) estimates are often done based on annual average values. The present research effort aims at large scale estimation of the energy use and carbon emissions due to domestic hot water consumption in two, predominantly residential, locations in a touristic region in Portugal. A novel dynamic modelling approach is proposed and used, which accounts for the variability of: i) the cold water temperature based on measured data; ii) the total amount of water consumed based on measured data; and iii) the fraction of the water consumed as domestic hot water corrected by the air temperature. The results are compared with alternative modelling approaches of the same degree of complexity, revealing differences ranging between −18% and +11% in both net energy required to produce the domestic hot water and the corresponding carbon emissions. Differences in the results are found to exist not only due to the modelling approach, but also between the locations, highlighting the importance of both the simulation approach and the particularities of the context being captured. Highlights: Domestic water consumption patterns in a touristic region are presented. Public network water temperature patterns are presented. Novel domestic hot water consumption estimation is proposed. Energy use for domestic hot water production is estimated. Carbon emissions from domestic hot water production are forecasted.